Fabrication of scalable, aligned and low density carbon nanotube/silicon carbide hybrid foams by polysilazane infiltration and pyrolysis. Issue 6 (June 2021) - Aly, Karim; Muhuri, Abir K.; Bradford, Philip D.
Abstract: Polymer-derived ceramic (PDC) process is an attractive technique that has high ceramic yield. This versatile method allows for fabrication of porous carbon nanotube (CNT)/ silicon carbide (SiC) hybrid materials that is important high temperature structural applications. Although several forms of CNT assemblies have been used with the PDC approach, the fabricated CNT/ceramic nanocomposites were either one or two dimensional. Herein, we report, for the first time, the fabrication of a low density, three-dimensional (3D) and scalable CNT/SiC structure using PDC technique. It was synthesized by impregnating preceramic polysilazane (PSZ) into ultralow density, anisotropic, and highly aligned CNT foams, followed by thermosetting and pyrolysis processes. The ceramic phase conformally coated the CNTs. The X-ray diffraction (XRD) diffractogram confirmed the presence of β-SiC crystalline phase. The resulting hybrid foam inherited the morphology and form factor of the original CNT foam, and possessed mechanical robustness, improved electrical properties, and extraordinary thermal stability.